The times and spaces of leadership development: (un)designing learning - Fatien Diochon, Pauline (2019)
The above quotation taps into something within the human condition that is potentiallyat least, very powerful. We, human beings, have aspirations; flying might be just one ofthem! But the central point here is that “the majority of people” often comply or silencetheir aspirations. In some contexts around the world, silence and compliance could beseen as the “rational” choice. However, even within great oppressive regimes, the humanspirit may shine through, and empowerment can potentially emerge.Our complex and dangerous times set the context for both tragedy and hope. Against thisbackdrop, this special issue of Cuadernos de Administracion explores the ways in whichleadership spirit can develop. To be more specific, we delve into this tension betweentragedy and hope through the four following main themes:• The spaces for learning• Crossing boundaries for learning• Timing in learning• Power dynamics in learning spaces